2005
DOI: 10.1521/soco.23.1.11.59195
|View full text |Cite
|
Sign up to set email alerts
|

False Memories About Food Can Lead to Food Avoidance

Abstract: In two experiments, we suggested to 336 participants that as children they had become ill after eating either hard-boiled eggs or dill pickles. Eighty-three additional control participants in Experiment 1 received no suggestion. In both experiments, participants' confidence increased in line with the suggestion. In the second experiment, we used a pretest/posttest design and found that enhanced confidence was accompanied by avoidance of the relevant food item. These results demonstrate that adults can be led t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 27 publications
3
64
1
1
Order By: Relevance
“…I was 100% clear!"). Whereas Wade and colleagues' false evidence actually depicted subjects performing the fictional act Nash & Wade, 2009;Wade et al, 2002), and other authors have used explicit and affirmative verbal feedback as evidence (Bernstein et al, 2005b;Desjardins & Scoboria, 2007), the false evidence in the present study was less explicit. Indeed, subjects neither saw themselves perform the critical actions, nor did they receive a verbal suggestion.…”
Section: Discussioncontrasting
confidence: 65%
“…I was 100% clear!"). Whereas Wade and colleagues' false evidence actually depicted subjects performing the fictional act Nash & Wade, 2009;Wade et al, 2002), and other authors have used explicit and affirmative verbal feedback as evidence (Bernstein et al, 2005b;Desjardins & Scoboria, 2007), the false evidence in the present study was less explicit. Indeed, subjects neither saw themselves perform the critical actions, nor did they receive a verbal suggestion.…”
Section: Discussioncontrasting
confidence: 65%
“…In terms of repercussions, we also found that those who believed the false suggestion (the believers, who comprised Ϸ30% of subjects) later avoided the critical food. By avoid, we mean that they told us that they were less inclined to want to eat the food at a party, and, more generally, they told us that they enjoyed the food less (8). These findings were among the first to suggest that false food memories can be created, and that those false memories might have behavioral consequences.…”
Section: The Consequences Of False Beliefmentioning
confidence: 99%
“…We falsely told experimental subjects that, as children, they had become ill after eating a certain food. We accomplished this in one study by specifically suggesting to some subjects that they had become ill after eating dill pickles and to other subjects that they had become ill after eating hard-boiled eggs (8).…”
Section: The Consequences Of False Beliefmentioning
confidence: 99%
“…she asked. Using the forced feedback technique, Loftus first attempted to make subjects believe they had become sick from eating either hard-boiled eggs or dill pickles (9). After these suggestions were planted, the subjects were asked to imagine being hungry at an outdoor barbecue and to pick which foods on the picnic table they wanted to eat.…”
Section: Power Of Strawberry Ice Creammentioning
confidence: 99%